Evaluating the Efficacy of Coronavirus Disease 2019 Vaccines. (18th December 2020) - Lin, Dan-Yu; Zeng, Donglin; Mehrotra, Devan V; Corey, Lawrence; Gilbert, Peter B
Abstract: A large number of studies are being conducted to evaluate the efficacy and safety of candidate vaccines against coronavirus disease 2019 (COVID-19). Most phase 3 trials have adopted virologically confirmed symptomatic COVID-19 as the primary efficacy end point, although laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is also of interest. In addition, it is important to evaluate the effect of vaccination on disease severity. To provide a full picture of vaccine efficacy and make efficient use of available data, we propose using SARS-CoV-2 infection, symptomatic COVID-19, and severe COVID-19 as dual or triple primary end points. We demonstrate the advantages of this strategy through realistic simulation studies. Finally, we show how this approach can provide rigorous interim monitoring of the trials and efficient assessment of the durability of vaccine efficacy. Abstract : To increase statistical power and meet vaccine success criteria, we propose to evaluate the efficacy of coronavirus disease 2019 (COVID-19) vaccines by using the dual or triple primary end points of severe acute respiratory syndrome coronavirus 2 infection, symptomatic COVID-19, and severe COVID-19.